La primauté du modèle de l’homme grec dans les manuels d’histoire du premier franquisme - Bertrand Noblet (Cahiers de Civilisation Espagnole Contemporaine)
In this article the author questions the nature of the role models proposed for young boys in the chapters about Antiquity found in their history books during the Second Republic and during the early Francoist period. In particular it poses the question: to what extent the change of regime may have influenced a mutation in masculine values. However, an analysis of the school history books of the period shows that if these heroes showed more martial values after 1939, the image of the ideal man hardly changed: it remained the Greek ideal, more particularly the Athenian citizen. To the men of the future the school books were proposing models, which were hardly orthodox if we compare them to the virile ideal of the monk-soldier, exalted by a dictatorial regime (founded by soldiers) which carried in its heart the ideals of the Falange. Without doubt the educational system, and those who worked within it, had their own system of values, which escaped, at least in part, the official culture.